Produção habitacional, agentes e território: uma análise do programa minha casa, minha vida na região metropolitana de Natal (2009-2014) - Ferreira, Glenda Dantas (2016)
This thesis deals with current issues related to contemporary Brazilian housing policies focusing the housing Program called Minha Casa, Minha Vida. It was seen that social housing production has been guided by real estate agents and set on a capitalist logic that is throughly supported by the State. These views are enphasized in a metropolitan scale which enables socio-spatial reproduction of families in the metropolization process. In practical terms, this reproduction occurs based on a socio-spatial organization model of the territory that in turn, is set on expressive social inquality related to the the commodification of land and housing. Thus, a standoff emerges between the scale of the phenomenon – - problematic Housing in terms of qualitative and quantitative déficit in the scale of operations of these municipalities; which are responsible for implementing housing programs. Thus, considering these issues, this work aims to enquire: How does the Minha Casa, Minha Vida program structure social interest housing production in the Metropolitan Region of Natal in Rio Grande do Norte in Brazil?. It is admited that this program is established and set on certain development condtions that foment new housing practises on behalf of real estate agents. These practises are mediated by the state and relate to real estate products and operation scales; considering their spatial performance Thus, the research investigates the Minha Casa, Minha Vida Program aiming to identify its current structure regarding social interest production, its mains characteristics in the Metropolitan Region of Natal. The work also deals with State and real estate agents; participants in the program´s implementation process. This is done considering the time period of 2009 to 2014. The study universe is delimited by the functional metropolis of Natal; formed by the cities of Natal, Parnamirim, São Gonçalo do Amarante, Macaíba and Extremoz. As for methodological procedures, a qualitative research with semi-structured interview was realized with municipal managers, representatives of the Caixa Econômica Federal Bank as well as civil construction companies. There was also a documental analysis that considered the program´s legislation and secondary data on housing production. The research identified a movement towards peripheral internalization of social housing production on behalf of real estate agents that have considered this metropolitan space as a reference. On the other hand, it was possible to perceive that housing public policies are organized based on local actions. The research results point to the occurrence of a real estate structuring process in the Functional Metropolis of Natal that in turn, are directed to the families of social interest by the Minha Casa, Minha Vida Program.